2012
DOI: 10.1029/2011jg001902
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic impact of typhoon waves on coral communities in the Ryukyu Islands under global warming

Abstract: [1] Typhoon-generated storm waves generally cause mechanical damage to coral communities on present-day reefs, and the magnitude and extent of damage is predicted to increase in the near future as a result of global warming. Therefore, a comprehensive understanding of potential future scenarios of reef ecosystems is of prime interest. This study assesses the current status of coral communities on Ibaruma reef, Ryukyu Islands, on the basis of field observations, engineering and fluid dynamic models, and calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Moreover, some Porites boulders in group 2 are clearly microatolls in the moat. Hongo et al (2012) reported that even the maximum possible storm waves that affect the reefs at Ishigaki Island have no wave force suffi cient to move microatolls of >40 cm in diameter in the moat, which are far smaller than the boulders observed in this study (>1 m diameter). Our preliminary survey revealed ~5-6-m-long living Porites coral colonies in the present moat of Ishigaki Island.…”
Section: Boulder Originmentioning
confidence: 69%
“…Moreover, some Porites boulders in group 2 are clearly microatolls in the moat. Hongo et al (2012) reported that even the maximum possible storm waves that affect the reefs at Ishigaki Island have no wave force suffi cient to move microatolls of >40 cm in diameter in the moat, which are far smaller than the boulders observed in this study (>1 m diameter). Our preliminary survey revealed ~5-6-m-long living Porites coral colonies in the present moat of Ishigaki Island.…”
Section: Boulder Originmentioning
confidence: 69%
“…Typhoon damage from direct physical disturbances, turbidity, sedimentation, and salinity changes can be destructive to shallow coral reefs and has been well studied (Van Woesik, Ayling & Mapstone, 1991; Harmelin-Vivien, 1994; Ninio et al, 2000; Cheal et al, 2002; Hongo, Kawamata & Goto, 2012). Declines in coral cover on shallow reefs (<25 m in depth) have been documented, specifically in genera such as Acropora , Montastraea , Porites , Agaracia , Diploria , Millepora , Siderastrea , Pocillopora , Pachyseris , Montipora , and Merulina (Harmelin-Vivien, 1994; Van Woesik, De Vantier & Glazebrook, 1995; Fabricius et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since mortality of both small and large colonies was found in this study, the effect of sedimentation could be a relevant factor affecting the population dynamics of A. japonica. As the small colony mortality was dominant, mortality could also be related to strong wave action during typhoons (Hongo et al 2012). Observations of coral skeletons on the seabed during the daytime surveys in November also suggest that some live colonies were removed by strong water flow occurring during typhoons.…”
Section: Resultsmentioning
confidence: 97%